miRNA Profiling of Circulating Small Extracellular Vesicles From Subarachnoid Hemorrhage Rats Using Next-Generation Sequencing - Lan, Shihai; Zhou, Lin; Wang, Yimei; Fang, Linchun; Yang, Le; Zheng, Suyue; Zhou, XinHui; Tang, Bin; Duan, Jian; Wu, Xiao; Yang, Chengxing; Hong, Tao (Frontiers in Cellular Neuroscience, 2020)
Background: Extracellular vesicles (EVs) are produced during abnormal and normal physiological conditions. Understanding the expression profile of microRNA in plasma-derived small extracellular vesicles (sEVs) and their roles subarachnoid hemorrhage (SAH) that cause cerebral vasospasm (CVS) is imperative. Methods: Sprague Dawley rats (250–300 g) were allocated to sham or SAH groups established using endovascular perforation method. miRNA expression profiles of plasma sEVs in both groups (each n = 4) were evaluated using next-generation sequencing (NGS). Results: There were 142 miRNAs significantly expressed differently between the two groups, of which 73 were up-regulated while 69 were down-regulated in SAH sEVs compared with those of sham (P<0.05; fold change ≥2). Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway and Gene Ontology (GO) analyses of differently expressed (DE) miRNAs revealed signaling pathways and target genes (TGs) in SHA group. rno-miR-185-5p, rno-miR-103-3p, rno-miR-15b-3p, rno-miR-93-5p and rno-miR-98-5p were the top five most up regulated sEVs miRNAs. Conclusion: Our results suggest that miRNA can be selectively packaged into sEVs under SAH, and this could help develop potential targets for prevention, diagnosis and treatment of CVS after this condition.